Knowledge Families Hold: Co‐Production and Co‐Research With Mental Health Family Carers in Understanding Experiences During the COVID‐19 Pandemic - Walters, Caroline; McDonald, Eileen; Sheers, Carli; Hawkins, Kerry; Solich, Hayley; Anderson, JulieAnne; Simic, Nevena; Moore, Danielle; Stevenson, Tony; Lawn, Sharon; Goodyear, Melinda; Maghidman, Marcelo; et al. (Health expectations : an international journal of public participation in health care and health policy, 2024)
ABSTRACT Background Through an in‐depth exploration of mental health family carers' experiences during the COVID‐19 pandemic in Australia, this co‐produced study identified recommendations for advocacy, practice and policy implications to uphold family carer wellbeing. Government‐enforced restrictions, changed service availability and difficulties accessing hospitals, led to additional anxiety, depression and elevated distress, especially for people experiencing mental health challenges before the pandemic. The National Mental Health Consumer and Carer Forum alongside two academic researchers aimed to discern the impact of care provision, levels of distress, unmet needs, challenges and benefits of providing support, across geographic locations and diverse communities. Methods This article reports on the survey component of a co‐designed mixed‐methods exploratory study of family carer experiences. A project steering group worked with two academic researchers, members of SWITCH Research Group, Monash University, to develop the 71‐question online survey across 9‐domains. Results Family carers were relied upon to provide support and care when mental health services changed or closed. Carers support more than one person and typically people with daily and high‐level needs. Caring levels increased from 26‐h to an average of 40‐h a week of support provision, with changed roles and increased complexity. Heightened demands became stress‐inducing to the point of mental ill health and suicidality for some family carers. Conclusion Government policy and pandemic responses failed to address the financial, practical or emotional resources needed to fulfil the role of care provision and support to unwell and extremely distressed people with new or ongoing mental and psychological ill‐health. Patient or Public Contribution From its inception, this project was co‐produced and co‐designed with mental health family carers and service users based on their expertise in understanding their experiences and ways to best explore these to the benefit and wellbeing of families in distress. The academic research partners both have active experience of supporting people with mental health challenges. Through each of the identified phases, lived experience expertise (family carers and service users) co‐designed and co‐facilitated the process. At times leading the process, such as in recruitment strategies, and at other times acting as guides. Guidance was provided by lived experience expertise in reflecting upon the literature review to understand what had been researched internationally and what would be important to understand in Australia. The academic partners advised on the possible processes for data collection, and the lived experience experts decided on the methodology based on that advice. Both the focus group and survey questions were developed and scrutinised from the perspective of the service users and carers in the project team. Difficult conversations were handled with respect, service users within the project team gently addressed areas of enquiry that may suggest stigma or feed into societal stereotypes of people with mental health challenges. Carers were able to consider the wording of questions to still be able to address areas of concern including domestic violence within the family unit and suicide. Dissemination strategies were planned together with the carer and service user representatives being co‐presenters at conferences. The report for submission to the National Mental Health Commission (Australia) was written and reviewed with all partners. A committee of service users and carers, alongside the academic partners, planned the launch of the report in August 2023. The co‐authorship of peer‐reviewed articles has included family carers and service users from the National Mental Health Consumer and Carer Forum.